2022
DOI: 10.7150/jca.65574
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutation and expression of BAP1 in hepatocellular carcinoma: an indicator for ferroptosis and immune checkpoint inhibitor therapies

Abstract: BRCA1-Associated Protein 1 (BAP1) is a deubiquitylase that is found associated with multiprotein complexes that regulate key cellular pathways, and subsequent researches have revealed that BAP1 acts independently as a tumor suppressor. Somatic BAP1 mutations occur in various malignancies, but malignancies arising from mutation of tumor suppressors have unexplained tissue proclivity. Whether somatic mutation or expression alteration of BAP1 in hepatocellular carcinoma (HCC) influence carcinogenesis or immunogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Therefore, these results detailed the conditions and ways in which FRGs regulate GC development, which may be conducive to further study of immune escape surveillance. In addition, ferroptosis-related reactive oxygen species and iron uptake could lead to somatic nonsynonymous mutations and microsatellite instability, resulting in increasing immunogenicity and immune infiltrates [47,48], which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, these results detailed the conditions and ways in which FRGs regulate GC development, which may be conducive to further study of immune escape surveillance. In addition, ferroptosis-related reactive oxygen species and iron uptake could lead to somatic nonsynonymous mutations and microsatellite instability, resulting in increasing immunogenicity and immune infiltrates [47,48], which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…LINC01419 overexpression inhibited FBP1 expression, and knockdown of LINC01419 promoted FBP1 expression. Studies have shown that FBP1 can inhibit the malignant progression of cancers such as hepatocellular carcinoma [35], cholangiocarcinoma [27], and breast cancer [36]. Dong et al showed that FBP1 deletion induces glycolytic processes, promotes EMT pathways in breast cancer cells as well as improves cell stemness in CSCs [36].…”
Section: Discussionmentioning
confidence: 99%
“…127,128 Loss of functional BAP1 is associated with tumorigenesis or BAP1 cancer syndrome, which involves uveal melanoma, mesothelioma, renal cell carcinoma (RCC), HCC, cutaneous melanoma, and breast cancer. [129][130][131] Further, the BAP1 expression has been lower in human lung adenocarcinoma samples than in normal samples and is positively correlated with patient survival. Observations in an animal model of lung adenocarcinoma demonstrated the reduction of BAP1 level during tumor growth that was associated with the reduction of KELCH-ECH-associated protein 1 (Keap-1) expression and increased nuclear factor E2-related factor-2 (Nrf-2, a redox-sensitive transcription factor) activity as well as suppression of oxidative stress.…”
Section: Deubiquitinasesmentioning
confidence: 96%
“…It also affects cell cycle proteins, mitochondrial function, cell survival, tumor metabolism, and immune responses 127,128 . Loss of functional BAP1 is associated with tumorigenesis or BAP1 cancer syndrome, which involves uveal melanoma, mesothelioma, renal cell carcinoma (RCC), HCC, cutaneous melanoma, and breast cancer 129–131 . Further, the BAP1 expression has been lower in human lung adenocarcinoma samples than in normal samples and is positively correlated with patient survival.…”
Section: The Role Of Ups Dysregulation In Tumorigenesismentioning
confidence: 99%